DERIVATIONS IN HEADLINE ARTICLES OF THE JAKARTA POST NEWSPAPER - Arbain Arbain (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2017)
This study aimed to see types of derivation, processes undergone, and structures of derived words. This study used content analysis selecting four headline articles from The Jakarta Post newspaper. The findings showed that three types of derivations: derivational prefix, derivational suffix, and multiple derivations were obtained. Each of derivation indicated 14 types of structures of derived words relating to derivation; 3 relating to derivational prefix, 3 types of  derivational suffix, and 8 types to multiple derivations. Relating to processes of derivations, there were class of maintaining derivation and class of changing derivation. Derivational prefix brought to change in meaning (class maintaining derivation) and derivational suffix caused the change both in meaning and category (class changing derivation).